PENERAPAN MODEL PEMBELAJARAN GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISTEM PENGAPIAN KONVENSIONAL - Ahfid Husni Mubarok; Samsul Hadi (Jurnal Taman Vokasi, 2016)
The aim of this research to determine the increase in activity and learning outcomes conventional ignition system by applying the learning model of Group Investigation (GI). The hypothesis in this research is application of Group Investigation (GI) learning model’s can increase the activity and learning outcomes conventional ignition system. The research is a Classroom Action Research (CAR) conducted collaboratively between teachers and researches. The subjects in this study is 20 students from class TKR of SMK, while the object of this research is the application of Group Investigation learning model’s (GI) to increase the activity and student learning outcomes in conventional ignition system subjects. The experiment was conducted with three (3) cycles. Data collection techniques using observation, testing and documentation. Data were analyzed using quantitative description of the statistical formula. Results of this research by applying the Group Investigation learning model’s (GI) showed the presence of increasing activity and learning outcomes conventional ignition system in every cycle. This is indicated by: 1. The increase of learning outcomes was showed by percentage of learning activity more than (≥) enough, before action only 25% increased by 22,4% into 47,4% after doing first cycles. When doing second cycles increased by 10,5% into 63,2% and third cycles increased by 10,5% into 73,7%. 2. Another increase was showed by learning outcomes of students who passed, from learning outcomes before action only 40% and after doing first cycles increased by 12,6% to 52,6%. Then second cycles increased by 8,5% into 61,1% and third cycles increased by 17,8% into 78,9%. From the above data it can be conclude by applying the learning model of Group Investigation (GI) on the subjects of conventional ignition system  can increase the activity and learning outcomes, in line with the hypotesis of this action research